2012
DOI: 10.1007/s10162-012-0315-6
|View full text |Cite
|
Sign up to set email alerts
|

Neural Coding of Sound Intensity and Loudness in the Human Auditory System

Abstract: Inter-individual differences in loudness sensation of 45 young normal-hearing participants were employed to investigate how and at what stage of the auditory pathway perceived loudness, the perceptual correlate of sound intensity, is transformed into neural activation. Loudness sensation was assessed by categorical loudness scaling, a psychoacoustical scaling procedure, whereas neural activation in the auditory cortex, inferior colliculi, and medial geniculate bodies was investigated with functional magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
53
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 44 publications
18
53
6
Order By: Relevance
“…Specifically, at cortical level, changes in sound pressure level were reflected by nonlinear (quadratic) increases of activation magnitude, with steeper slopes at the highest sound levels. While this is in agreement with some previous findings (Hart et al 2002(Hart et al , 2003, other studies reported a more or less linear increase of BOLD signal strength with sound intensity (Hall et al 2001;Langers et al 2007;Röhl and Uppenkamp 2012) and still others found indications of response saturation at the highest levels (Mohr et al 1999). To what extent these differences can be explained in terms of the use of different types of stimuli, dynamic ranges, fMRI paradigms or other factors (e.g., perceived loudness) is an interesting topic by itself, but this is not the scope of the present study.…”
Section: Response Characteristics In Relation To Sound Intensitysupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, at cortical level, changes in sound pressure level were reflected by nonlinear (quadratic) increases of activation magnitude, with steeper slopes at the highest sound levels. While this is in agreement with some previous findings (Hart et al 2002(Hart et al , 2003, other studies reported a more or less linear increase of BOLD signal strength with sound intensity (Hall et al 2001;Langers et al 2007;Röhl and Uppenkamp 2012) and still others found indications of response saturation at the highest levels (Mohr et al 1999). To what extent these differences can be explained in terms of the use of different types of stimuli, dynamic ranges, fMRI paradigms or other factors (e.g., perceived loudness) is an interesting topic by itself, but this is not the scope of the present study.…”
Section: Response Characteristics In Relation To Sound Intensitysupporting
confidence: 93%
“…To what extent these differences can be explained in terms of the use of different types of stimuli, dynamic ranges, fMRI paradigms or other factors (e.g., perceived loudness) is an interesting topic by itself, but this is not the scope of the present study. As opposed to AC, activation in the investigated subcortical structures increased predominantly linearly with increasing sound pressure level, which is in line with previous findings (Röhl and Uppenkamp 2012). Our findings further suggest considerable differences along the auditory pathway and across auditory regions in cortex with respect to the strength of the relationship between neural activity and sound intensity.…”
Section: Response Characteristics In Relation To Sound Intensitysupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it might support the notion that sounds delivered to one ear are predominantly processed in the contralateral hemisphere. Given that our fMRI results show enhanced activity in STG contralateral to the sound-triggering hand, and that activity in STG has been shown to correlate with perceived loudness 27 , we looked for differences in monaural hearing thresholds for stimuli triggered by the different hands. Right ear stimulation evokes activity in the auditory cortex which is biased to the left hemisphere, and our fMRI results indicate stronger fMRI signal in left STG during playing with the right versus the left hand.…”
Section: Discussionmentioning
confidence: 99%
“…Since fMRI activity in the auditory cortex has been previously shown to correlate with perceived loudness of auditory stimuli 27 , in an additional set of behavioural experiments we examined whether the fMRI results in our study also have a behavioural correlate of increased hearing sensitivity. First, we performed an experiment in which we assessed binaural hearing thresholds to a 1-kHz pure-tone in 16 subjects during active and passive conditions (see Methods for details).…”
mentioning
confidence: 92%